Tumor-Derived Autophagosomes (DRibbles) Activate Human B Cells to Induce Efficient Antigen-Specific Human Memory T-Cell Responses - Ren, Hongyan; Zhang, Tianyu; Wang, Yongren; Yao, Qi; Wang, Ziyu; Zhang, Luyao; Wang, Lixin (Frontiers in Immunology, 2021)
We have reported that tumor-derived autophagosomes (DRibbles) were efficient carriers of tumor antigens and DRibbles antigens could be present by DRibbles-activated B cells to stimulate effect and naïve T cells in mice. However, the effect of DRibbles on human B cells remains unclear. Herein, we found that DRibbles can also efficiently induce proliferation and activation of human B cells and lead to the production of chemokines, cytokines and hematopoietic growth factors. We further demonstrated human B cells can effectively phagocytose DRibbles directly and cross-present DRibbles antigens to stimulate antigen-specific memory T cells. Furthermore, we found that membrane-bound high-mobility group B1 (HMGB1) on DRibbles was crucial for inducing human B cells activation. Therefore, these findings provide further evidence to promote the clinical application of B-DRibbles vaccines.